Biphasic liquid interface derived magnetite nanocrystals: synthesis, properties and growth mechanism. (14th December 2017) - Hou, Yue; Hou, Chuanxin; Fan, Yuqi; Dang, Feng; Li, Bao-Wen
Abstract: Magnetite (Fe3 O4 ) nanocubes were synthesized from a water-toluene biphasic liquid system. The Fe3 O4 nuclei generated in aqueous phase were transferred into the toluene solution by modifying oleic acid (OLA) at the organic–inorganic interface. Well-dispersed Fe3 O4 nanocubes with a size of 20 nm were prepared in this process. Octylamine was found to play a dominant role in controlling the dispersibility, morphology and particle size of nanocubes. Only alkylamine with proper chain length had effects on the morphology control in the biphasic liquid synthesis system. The remanence (7.04 emu g −1 ) and coercivity (170 Oe) of the nanocubes were 3 times higher than those (the remanence and coercivity value were 2.03 emu g −1 and 68 Oe) of irregular particles. Magnetite (Fe3 O4 ) iron oxide nanoparticles can be used in various fields, including developing biomarker detection systems for disease diagnosis, ferrofluids, drug delivery, magnetic resonance imaging (MRI), energy storage, sensing, etc.